2015
DOI: 10.1039/c5ra08778c
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive activity of a quinoline appended chalcone derivative and its site specific binding interaction with a relevant target carrier protein

Abstract: The usefulness of heterocyclic chalcone derivative as a therapeutic target in controlling hypertension and its site specific binding interaction with model transport protein to get a clear picture about its delivery mechanism. AbstractInhibition of Angiotensin Converting Enzyme (ACE) is identified as a main therapeutic target in controlling hypertension. The principal intent of this work is to investigate the ACE inhibitory property of a quinoline appended chalcone derivative (E)-3-(anthracen-10-yl)-1-(6,8-dib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 72 publications
(112 reference statements)
0
31
0
Order By: Relevance
“…Several commercial drugs such as Primaquine ® , Plasmoquine ® , Mefloquine ® , Chloroquine ® , OSI-930, and Saquinavir ® incorporate quinoline pharmacophore [ 14 , 15 ]. A range of quinoline derivatives have been reported for their analgesic [ 16 ], antifungal [ 17 ], antibacterial [ 18 ], antioxidant [ 19 ], anticancer [ 20 , 21 ], anti-inflammatory [ 22 ], antiviral [ 23 , 24 ], anti-Alzheimer [ 25 ], cytotoxic [ 26 ], antileishmanial [ 27 , 28 ], and anti-hypertensive activities [ 29 , 30 ]. Similarly, piperidine ring is also prevalent in numerous naturally occurring alkaloids [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several commercial drugs such as Primaquine ® , Plasmoquine ® , Mefloquine ® , Chloroquine ® , OSI-930, and Saquinavir ® incorporate quinoline pharmacophore [ 14 , 15 ]. A range of quinoline derivatives have been reported for their analgesic [ 16 ], antifungal [ 17 ], antibacterial [ 18 ], antioxidant [ 19 ], anticancer [ 20 , 21 ], anti-inflammatory [ 22 ], antiviral [ 23 , 24 ], anti-Alzheimer [ 25 ], cytotoxic [ 26 ], antileishmanial [ 27 , 28 ], and anti-hypertensive activities [ 29 , 30 ]. Similarly, piperidine ring is also prevalent in numerous naturally occurring alkaloids [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, changes in the CD signals of the protein upon incubation with different amounts of compound 1 showed a perturbation in the α‐helical structure of the protein template (Figure c), which suggested that the probe molecule had become embedded in the α‐helices of subdomain IIA of HSA . FTIR analysis also revealed that stretching frequencies related to the α‐helices of the protein (amide I, OH, and NH bands) were affected during the interaction with compound 1 (see the Supporting Information, Figures S13 and S14) …”
Section: Resultsmentioning
confidence: 99%
“…[55,56] FTIR analysisa lso revealed that stretching frequencies related to the a-helices of the protein (amide I, OH, and NH bands) were affected during the interaction with compound 1 (see the Supporting Information, Figures S13 and S14). [57,58] Because pH value had ap ronounced influence on the assembly behavior of compound 1,w ea lso investigated the effect of pH value on its albumin-sensing properties. The emission spectrum of compound 1 at pH 6.0 clearly showed aggregate emission, with am aximum at l = 454 nm.…”
Section: Resultsmentioning
confidence: 99%
“…3-Acylquinolines have been reported to possess herbicidal activity 46 as well as antihypertensive activity. 47 Some efficient methods for the preparation of 3-acylquinolines have been developed, such as Pd-catalyzed carbonylative Suzuki crosscoupling reactions of arylboronic acid with 3-iodoquinoline, 48 Pd-catalyzed coupling of aldehydes and 3-bromoquinoline 49 or arylboronic acid and 3-quinolinecarbaldehyde, 50 Fe-catalyzed cascade Michael addition/cyclization of o-aminoaryl aldehydes/ketones/alcohols with ynones, 45 and domino reactions between N,N-dimethyl enaminones and anilines. 41 In addition, dehydrogenation of saturated carbonyl compounds to afford a,b-unsaturated carbonyl derivatives has been found to be compatible with other organic transformations, leading to efficient one-pot protocols for the synthesis of functionalized molecules.…”
Section: Introductionmentioning
confidence: 99%